2015
DOI: 10.1109/tvt.2014.2339271
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Coordination in Energy-Efficient Cognitive Radio Networks

Abstract: Device coordination in open spectrum systems is a challenging problem, particularly since users experience varying spectrum availability over time and location. In this paper, we propose a game theoretical approach that allows cognitive radio pairs, namely the primary user (PU) and the secondary user (SU), to update their transmission powers and frequencies simultaneously. Specifically, we address a Stackelberg game model in which individual users attempt to hierarchically access to the wireless spectrum while… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…(Stackelberg Equilibrium [ 30 ]). The vector of Action Space basically is a Stackelberg Equilibrium if and only if: satisfies, where , and also …”
Section: System Description and Problem Formulationmentioning
confidence: 99%
“…(Stackelberg Equilibrium [ 30 ]). The vector of Action Space basically is a Stackelberg Equilibrium if and only if: satisfies, where , and also …”
Section: System Description and Problem Formulationmentioning
confidence: 99%
“…The second term in (43) can be bounded by using the same technique in [20] (page [26][27][28]. Let us substitute inequality (32) into (44), and then substitute (44) into equation (43) and sum over n. Use the fact that the sum of expectation on u and q t with respect toΦ t (j) is less than E It∼p tΦ t (j). Take expectation over all random strategies of losses up to time n, we obtain…”
Section: A the Adversarial Regimementioning
confidence: 99%
“…In a prior work [21], we proposed a hierarchical game theoretic model for two-user-two-carrier energy efficient wireless systems. It was shown that, for the vast majority of cases, users choose their transmitting carriers in such a way that if the leader transmits on a given carrier, the follower has incentive to choose the other carrier.…”
Section: Related Literature and Novelty Of The Workmentioning
confidence: 99%
“…It was shown that, for the vast majority of cases, users choose their transmitting carriers in such a way that if the leader transmits on a given carrier, the follower has incentive to choose the other carrier. One major motivation of this paper is to extend the original problem in [21] to some general models that can be widely used in practice by considering an arbitrary number of carriers.…”
Section: Related Literature and Novelty Of The Workmentioning
confidence: 99%